PENGARUH RISIKO BISNIS DAN PERTUMBUHAN PERUSAHAAN TERHADAP STRUKTUR MODAL DAN NILAI PERUSAHAAN - I Made Suadnyana; Luh Putu Wiagustini (Forum Manajemen STIMI Handayani Denpasar, 2013)
This study aims to ﬁ nd out the inﬂ uence of business risk and ﬁ rm growthtoward capital structure and the value of the ﬁ rm. The population of this study wasall go public of industrial companies registered at The Indonesian Capital Marketfrom 2008 up to 2010. We use the path analisys technic to evaluate the relationsamong variables of non ﬁ nancial industrial companies. While the direct and indirect impact of these variables were also observed.The result shows that business risk and ﬁ rm growth have different impact towardboth capital structue and value of the ﬁ rm. The ﬁ rst regression shows that businessrisk has negatively signiﬁ cant inﬂ uence on capital structure and ﬁ rm growth haspositively signiﬁ cant inﬂ uence on capital structure. The second regression showsthat bussiness risk has negatively signiﬁ cant inﬂ uence and ﬁ rm growth has positivelysigniﬁ cant inﬂ uence on ﬁ rm value. This study also conﬁ rm that capital structure haspositively signiﬁ cant inﬂ uence on the ﬁ rm value.